Patterns of engrailed protein in early Drosophila embryos. - Karr, T.L.; Weir, M.P.; Ali, Z.; Kornberg, T. (Development, 1989)
By the onset of gastrulation during nuclear cycle 14 of Drosophila embryogenesis, the engrailed gene is expressed in fourteen one-cell-wide stripes. Each stripe defines the anlagen of the posterior compartment of a metameric segment. We report here several observations relating to the role and disposition of the engrailed protein during the embryonic stages that precede cellularization. We demonstrate that in embryos mutant for the engrailed gene, there were characteristic morphological abnormalities as early as the 6th cleavage cycle. In addition, the engrailed protein was detected in pre-cycle-9 embryos by Western blot analysis. When localization of engrailed protein begins during cycle 14, engrailed expression was first present in broad anterior and posterior regions before the fourteen-stripe pattern appeared.